Analysis of Factors Influencing Preferences of Chinese Ethnic in Choosing Sharia Banks in Banda Aceh - Yani Prihatina Eka Furda; Fitria (SIASAT, 2022)
This study wanted to determine the effect of the preferences of the Chinese in Banda Aceh on the selection of Islamic banks. As well as wanting to know which Islamic bank is the most chosen by the ethnic Chinese to save their money, the research method used is the distribution of questionnaires to the ethnic Chinese in Banda Aceh. By using the Slovin formula, the sample of this study was 71 respondents. The results showed that of the 6 variables, namely service quality (X1) product (X2), location (X3), promotion (X4), facilities (X5), and information technology (X6) had different results. The service quality variable (X1) product (X2) promotion (X4) has no effect on choosing a Sharia Bank (Y), while location (X3), facilities (X5), and information technology (X6) have an effect on choosing a Sharia Bank (Y). Based on the results of distributing questionnaires to 71 ethnic Chinese respondents, the results showed that 70% of ethnic Chinese chose to save at BCA Syariah banks, 14% Aceh Syariah Banks, 10% BSI and the remaining 6% saved at other banks.